2022
DOI: 10.51253/pafmj.v72i1.6415
|View full text |Cite
|
Sign up to set email alerts
|

Acute-On-Chronic Liver Failure-Outcome and Its Predictors in A Tertiary Care Hospital

Abstract: Objective: To determine the characteristics and outcome of acute-on-chronic liver failure patients being managed at PakEmirates Military Hospital Rawalpindi. Study Design: Cross-sectional study. Place and Duration of Study: Department of Gastroenterology at Pak-Emirates Military Hospital, Rawalpindi, from Sep 2018 to Jan 2021. Methodology: In this study, 1559 patients diagnosed with cirrhosis were studied. Patients with pre-existing chronic kidney disease, chronic obstructive pulmonary diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…Similarly, Saxena et al (2020) [ 13 ] and Behera et al (2021) [ 17 ] also documented that alcohol was the most common etiology of CLD, followed by HBV and HCV. Saad et al (2022) [ 15 ] reported a high prevalence of HCV at 78%, similar to the current study. The differences in etiological factors across studies underline the geographical and demographic variability in CLD causation.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similarly, Saxena et al (2020) [ 13 ] and Behera et al (2021) [ 17 ] also documented that alcohol was the most common etiology of CLD, followed by HBV and HCV. Saad et al (2022) [ 15 ] reported a high prevalence of HCV at 78%, similar to the current study. The differences in etiological factors across studies underline the geographical and demographic variability in CLD causation.…”
Section: Discussionsupporting
confidence: 91%
“…Shin et al [ 14 ], in their study, recorded a median age of 54.8 years among participants, noting it did not markedly influence mortality rates (Hazard Ratio (HR) 1.00, 95% Confidence Interval (CI): 0.98-1.03, p=0.828) [ 14 ]. Saad et al (2022) [ 15 ] reported a higher mean age of 62 ± 7.2 years. Kulkarni et al (2018) [ 16 ] observed median ages of 42 years for those who survived and 47 years for those who did not (p=0.667) [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations